Between Adherence to Madhhab and Adaptation to Context: Fatwās on Female Leadership in Nahdlatul Ulama-Affiliated Islamic Higher Education Institutions - Hannan, Nur; Huda, M. Syamsul; Firdaus, Mohamad Anang; Afabih, Abdillah; Musthofa, Yayan (Journal of Islamic Law, 2024)
The issue of women in leadership has been a longstanding topic of debate among classical Islamic jurists, eliciting diverse responses from mainstream Islamic organizations in Indonesia. This article presents a comparative analysis of fatwās (Islamic legal opinions) issued by the Forum of Bahtsul Masail (FBM) at two Nahdlatul Ulama (NU)-affiliated Islamic higher education institutions: Ma’had Aly Hasyim Asy’ari Tebuireng, which prohibits female leadership, and Ma’had Aly Salafiyah Syafi’iyah Situbondo, which permits it. Through a combination of literature-based and empirical approaches, the article highlights a significant contrast in the istinbāṭ al-aḥkām (derivation of legal rulings) employed by these two FBMs. FBM Ma’had Aly Hasyim Asy’ari Tebuireng adopts the qawlī (literal) method, adhering to the majority views of classical Islamic jurists. In contrast, FBM Ma’had Aly Salafiyah Syafi’iyah Situbondo employs a manhājī (methodological) approach, incorporating minority opinions and reinterpreting texts within the context of modern societal changes. These contrasting fatwās reflect a broader tension between taqlīd (adherence to precedent) and adaptation to evolving social contexts. Furthermore, this article argues that the educational backgrounds of the FBM actors, as well as the curricula taught in their respective pesantren (Islamic boarding schools), contribute to the differences in fatwās. These differences reflect the internal dynamics within the fatwā production process in NU. [Isu kepemimpinan perempuan telah lama menjadi topik perdebatan di kalangan ahli hukum Islam klasik yang telah memicu beragam respons di kalangan organisasi masyarakat Islam arus utama di Indonesia. Artikel ini menganalisis secara komparatif fatwa dari Forum Bahtsul Masail (FBM) di dua ma’had aly yang berafiliasi dengan Nahdlatul Ulama (NU): Ma’had Aly Hasyim Asy’ari Tebuireng, yang melarang perempuan menjadi pemimpin, dan Ma’had Aly Salafiyah Syafi’iyah Situbondo, yang memperbolehkannya. Artikel ini, dengan mengombinasikan pendekatan kepustakaan dan empiris, menemukan bahwa kedua FBM menggunakan metode penggalian hukum (istinbāṭ al-aḥkām) yang berbeda. FBM Ma’had Aly Hasyim Asy’ari Tebuireng menerapkan metode qawlī, merujuk pada pendapat mayoritas ulama fikih, sementara FBM Ma’had Aly Salafiyah Syafi’iyah Situbondo menggunakan metode manhājī, mengadopsi pendapat ulama minoritas dan melakukan interpretasi (ulang) terhadap teks. Perbedaan fatwa tersebut dipengaruhi oleh pendekatan yang berbeda antara taklid dalam bermazhab dan adaptasi terhadap perubahan sosial. Lebih jauh, artikel ini berargumentasi bahwa latar belakang pendidikan para aktor FBM, serta kurikulum yang diajarkan di masing-masing pesantren, berkontribusi pada perbedaan fatwa yang dihasilkan. Perbedaan-perbedaan ini mencerminkan dinamika internal dalam proses produksi fatwa di kalangan NU.]